2021
DOI: 10.1002/ajb2.1758
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in Louisiana Iris species reveals patterns of recent and historical admixture

Abstract: Premise When divergent lineages come into secondary contact, reproductive isolation may be incomplete, thus providing an opportunity to investigate how speciation is manifested in the genome. The Louisiana Irises (Iris, series Hexagonae) comprise a group of three or more ecologically and reproductively divergent lineages that can produce hybrids where they come into contact. We estimated standing genetic variation to understand the current distribution of population structure in the Louisiana Irises. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…To date, genomic studies have confirmed the hybrid origin of the Oxford ragwort ( Senecio squalidus ) from the two Senecio species on Mt. Etna described above ( Nevado et al., 2020 ), identified several potential new cases of homoploid hybrid speciation (e.g., Grünig et al., 2021 ; Wang et al., 2021b ; Wang et al., 2022 ), suggested a difference in hybrid ancestry for two of the three well-studied sunflower homoploid hybrid species ( Owens et al., 2023 ), and failed to support several previously hypothesized examples of homoploid hybrid speciation, including Iris hexagona ( Zalmat et al., 2021 ) and two cases from Phlox ( Goulet-Scott et al., 2021 ).…”
Section: Speciation With Gene Flow Introgression and Hybrid Speciationmentioning
confidence: 77%
“…To date, genomic studies have confirmed the hybrid origin of the Oxford ragwort ( Senecio squalidus ) from the two Senecio species on Mt. Etna described above ( Nevado et al., 2020 ), identified several potential new cases of homoploid hybrid speciation (e.g., Grünig et al., 2021 ; Wang et al., 2021b ; Wang et al., 2022 ), suggested a difference in hybrid ancestry for two of the three well-studied sunflower homoploid hybrid species ( Owens et al., 2023 ), and failed to support several previously hypothesized examples of homoploid hybrid speciation, including Iris hexagona ( Zalmat et al., 2021 ) and two cases from Phlox ( Goulet-Scott et al., 2021 ).…”
Section: Speciation With Gene Flow Introgression and Hybrid Speciationmentioning
confidence: 77%
“…Extracted DNA from the broader collection of mussels ( n = 378 [ 19 ]) was used to create a reduced-complexity genomic library. This library included the 14 tissue and 14 swab replicates utilized here and was generated following modified protocols commonly used in our laboratory group across a wide diversity of species [ 5 , 19 , 20 , 21 , 22 ]. Restriction enzymes EcoRI and MseI were used to digest extracted DNA; EcoRI adapters (i.e., 10–20 base-pair multiplex identifier sequences: MIDs) were ligated onto the resulting fragments, and the 14 swab and 14 tissue replicates were each assigned unique barcodes.…”
Section: Methodsmentioning
confidence: 99%
“…Homoploid hybrid speciation is the process by which a new species is formed through hybridization of divergent parent lineages, but without an increase in ploidy (Grant, 1981;Rieseberg, 1997). Although several potential homoploid hybrid species are known in various plant groups-for example, Carex (Hodel et al, 2022), Senecio (James and Abbott, 2005;Brennan et al, 2012), Iris (Arnold, 1993;Taylor et al, 2013;Zalmat et al, 2021), Pinus (Wang and Szmidt, 1994), Penstemon (Wolfe et al, 1998), and Paeonia (Pan et al, 2007)-they appear to be somewhat rare in nature (but see Nieto Feliner et al, 2017). Results of the present study suggest that V. pallidum is an additional example.…”
Section: On Homoploid Hybridsmentioning
confidence: 99%